Assessing Anthropogenic Pressure through Biomonitoring: Aquatic Biota as Indicators of Water Quality in an Urban Lake - Nurvita Cundaningsih; Haerul Anwar; Faisal M Jasin; Hartono Hartono; Adrian Rahmat Nur; Rinaldi Idroes (CV FOUNDAE, 2025)
Urban areas in Jakarta face significant pressure on clean water resources due to increasing population and anthropogenic activities. This research aims to conduct biomonitoring of the Situ Bambon Ciracas lake ecosystem, East Jakarta, by analyzing water quality and the community structure of macrozoobenthos, phytoplankton, and zooplankton as bioindicators. A descriptive quantitative method was used, involving measurements of water physical-chemical parameters (TDS, TSS, pH, BOD, COD, Total-P) and identification of aquatic biota. The results indicate that the water quality of Situ Bambon Ciracas lake is lightly to moderately polluted, dominated by organic compounds. BOD (5−34.67 mg/L) and COD (17.05−193.56 mg/L) values consistently exceeded the Class 3 water quality standards, and TDS showed an increasing trend. The biota community structure reflects these conditions: macrozoobenthos showed moderate diversity (H′=1.2, E=0.6). Phytoplankton (H′=3.12−3.2, E=0.74−0.76) and zooplankton (H′=2.11−2.16, E=0.76−1.95) showed high diversity and evenness, but were dominated by bioindicator species tolerant to organic pollution (e.g., Oscillatoria sp., Nitzschia sp., Colpoda sp., Closterium sp.). The positive correlation between the abundance of these bioindicator species and high BOD and COD confirms organic waste as the main driver of ecological change. In conclusion, the Situ Bambon Ciracas lake ecosystem is under significant anthropogenic pressure. The dominance of pollution-tolerant species, despite existing diversity, highlights the urgency of comprehensive management and restoration efforts to maintain the sustainability of this urban lake.